2018
DOI: 10.1002/bit.26562
|View full text |Cite
|
Sign up to set email alerts
|

Anodic electro‐fermentation: Anaerobic production of L‐Lysine by recombinant Corynebacterium glutamicum

Abstract: Microbial electrochemical technologies (MET) are promising to drive metabolic processes for the production of chemicals of interest. They provide microorganisms with an electrode as an electron sink or an electron source to stabilize their redox and/or energy state. Here, we applied an anode as additional electron sink to enhance the anoxic metabolism of the industrial bacterium Corynebacterium glutamicum through an anodic electro-fermentation. In using ferricyanide as extracellular electron carrier, anaerobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 38 publications
(55 reference statements)
1
38
0
Order By: Relevance
“…Glucose was consumed over a period of 25 hr and concentrations of up to 70 mM lactate, 10 mM succinate, and 2 mM lysine were produced in the system (Figure b). Specific production rates were 1.7 mmol/g CDW /h lactate, 0.25 mmol/g CDW /h succinate, and 0.047 mmol/g CDW /h lysine, which are in the same range as in the 350 ml system (1.5 mmol/g CDW /h lactate, 0.25 mmol/g CDW /h succinate and 0.076 mmol/g CDW /h lysine) previously reported by Vassilev et al ().…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Glucose was consumed over a period of 25 hr and concentrations of up to 70 mM lactate, 10 mM succinate, and 2 mM lysine were produced in the system (Figure b). Specific production rates were 1.7 mmol/g CDW /h lactate, 0.25 mmol/g CDW /h succinate, and 0.047 mmol/g CDW /h lysine, which are in the same range as in the 350 ml system (1.5 mmol/g CDW /h lactate, 0.25 mmol/g CDW /h succinate and 0.076 mmol/g CDW /h lysine) previously reported by Vassilev et al ().…”
Section: Resultssupporting
confidence: 78%
“…Finally, the anaerobic bioelectrochemical production of lysine and organic acids using C. glutamicum was performed in the reported electrobioreactor. Comparable results to another electrobioreactor were achieved providing that the designed electrobioreactor is suitable for bioelectrochemical production of chemicals (Vassilev et al, ).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The interaction between microbes and a carbon electrode has been reported to alter the microbial intracellular redox balance, shifting the conversion process towards a more reduced or oxidized state . Previous studies have shown that electrode‐based regulation triggered a change in the metabolic (carbon) fluxes, and concurrently produced more reduced/oxidized metabolites, such as 3‐hydroxypropionic acid, l ‐lysine, and acetoin . EF provides a potential platform to further improve the titer and yield, particularly for targeted oxidized/reduced products in biochemical reactions, which are difficult to achieve through conventional fermentation …”
Section: Introductionmentioning
confidence: 99%